Walking the Eco-Talk Movement: Higher Education Institutions as Sustainability Incubators. (March 2014) - Collins, Denis; Gannon, Amy
Management scholars can have a major impact on advancing environmental sustainability by focusing on their own home institutions. A "four-type" sustainability action model is presented to foster thinking about how professors can engage and empower students, faculty, and staff to be active environmental change agents on their own campuses and local community. Faculty can assign sustainability class projects, integrate sustainability throughout the Business School's core curriculum, participate on a campus sustainability committee, and conduct research on sustainability in higher education that flows out of these activities. Some examples of these different types of efforts are offered based on experiences at Edgewood College, a small U.S. Midwestern college. A coordinated effort among faculty engaged in similar activities on other campuses would dramatically advance environmental sustainability.